Exodus : a commentary on the Greek text of Codex Vaticanus - Gurtner, Daniel M. (Septuagint commentary series., 2013)
In Exodus: A Commentary on the Greek Text of Codex Vaticanus, Gurtner provides an introduction and comprehensive commentary on the Greek text.